PARADIGMA BEMBELAJARAN ERA DIGITAL DI SEKOLAH TINGGI AGAMA ISLAM BAHRIYATUL ULUM K.H. ZAINUL ARIFIN PANDAN - Ismail, Ismail; Sukoco, Sugeng; Herianto, Herianto; Mesiono, Mesiono (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to explore the extent of the paradigm in learning adopted by the Bahriyatul Ulum K.H. Zainul Arifin Pandan Islamic College during the digital era as it is today. The descriptive method is a method used by researchers in analyzing data obtained through interviews, observations and documentation. The results of this study include: 1). Research-based learning by emphasizing lecturers and students so that in every learning they obtain research products / results as a form of contributing thoughts. 2). Multidirectional learning by making all media and other elements as learning resources. Lecturers are only as good as the corridors of lectures. 3). Monomedia learning becomes multimedia by utilizing aspects of learning as a means of supporting learning. 4). Group-based learning.Keyword: Learning Paradigm, Digital Era.